Penyerahan Bantuan Logistik Terpadu dan Pendampingan Distribusi Tepat Sasaran Korban Bencana Banjir di Kabupaten Aceh Tamiang - Hastuti, Mona; Apriliani, Apriliani; Ahsani, Afiatika; Tarigan, Rinawati; Melba, Restu Arahman; Nisa, Widiya; Zuhair, Ruslan; Mawaddah, Armi; Budiarti, Tri; Yuningsih, Yuningsih; Ismayadi, Ismayadi; Anwar, Syahferi; Nasution, Rafi Ahmad Rizal; Susanti, Susanti (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
The impacted community's basic requirements have not been met as a result of the natural disaster that struck Aceh Tamiang Regency. In order to guarantee that aid is targeted, particularly for vulnerable populations (toddlers, pregnant and breastfeeding mothers, the elderly, and individuals with disabilities), the Community Service program aims to distribute integrated logistical assistance and give distribution assistance. Benua Raja Village, Bukit Tempurung Village, Purwodadi Village, and Rantau Village were the four impacted villages where this exercise was carried out on December 7, 2025. Involving the community and volunteers, the strategies employed included gathering and delivering logistical support, distributing bundles of necessities, and offering distribution support all the way to the end. The activity's findings show that, in spite of obstacles brought on by difficult environmental circumstances and restricted access, community-based distribution and the integrated logistics package approach can increase assistance distribution's accuracy, transparency, and accountability. This program not only provides for the basic requirements of the community but also enhances local volunteer talents and humanitarian networks. Aid distribution was more successful thanks to the integrated logistical strategy and field support, which may be repeated in subsequent flood situations. It is intended that this initiative will serve as a template for adaptable and long-lasting community service approaches to disaster relief